2012
DOI: 10.1002/app.38573
|View full text |Cite
|
Sign up to set email alerts
|

Morphology study of immiscible polymer blends in a vane extruder

Abstract: This study reports the morphology development of polymer blends in a novel vane extruder in which polymer mainly suffers from elongational deformation field. Rapidly cooled samples of polypropylene/polystyrene (PP/PS) are collected in the vane extruder after stable extrusion. Furthermore, the shape and size of the dispersed phase from initial to final stages are analyzed. In addition, in order to compare the final size of the dispersed phase, different immiscible blends, including polypropylene/polyamide and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…At present, a number of reports [12][13][14][15][16] have been dedicated to the study of the resulting elongational flow. Furthermore, Qu et al [17,18] have proved that a vane extruder can cause a material to undergo large elongational deformation and has better efficiency of disperse mixing by numerous experiments. In this article, the mixing characteristics are theoretically derived.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a number of reports [12][13][14][15][16] have been dedicated to the study of the resulting elongational flow. Furthermore, Qu et al [17,18] have proved that a vane extruder can cause a material to undergo large elongational deformation and has better efficiency of disperse mixing by numerous experiments. In this article, the mixing characteristics are theoretically derived.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, PLA was blended with PP using a novel vane extruder based on an elongation force field with better mixing effect [28,29] and the mechanical properties, morphologies, crystallization behavior and thermal stability of the blends were investigated. Furthermore, the compatibilizers, maleic anhydride-grafted PP (MAPP) and ethylene/ n -butyl acrylate/glycidyl methacrylate terpolymer (PTW), were applied to improve the compatibility between PLA and PP in the blends.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research results have shown that vane extruder (VE) composed of several vane plasticizing conveying units 23 is based on the positive displacement conveying mechanism dominated by extensional deformation, which has many advantages such as stable output, better dispersive, and distributive mixing, reduced melt temperature, wide adaptability. The morphology development [24][25][26] of polymer blends was studied on this type of extruder. The results show that the extensional deformation generated in this type of VE can improve the mixing performance.…”
Section: Introductionmentioning
confidence: 99%